Si-doped Fe2O3 nanotubular/nanoporous layers for enhanced photoelectrochemical water splitting - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2013)
The present work reports the enhancement of the photoelectrochemical water splitting performance of in-situ silicon (Si)-doped nanotubular/nanoporous (NT/NP) layers. These layers were grown by self-organizing anodization on Fe-Si alloys of various Si content. The incorporation of Si is found to retard the layer growth rates, leads to a more pronounced nanotubular morphology, and most importantly, an improved photoelectrochemical behavior. By increasing Si content from 1, 2 to 5 at.% in the iron oxide NT/NP photoanodes, the photocurrent onset potential shifts favorably to lower values. At 1.3 V vs. RHE, hematite layer with 5 at.% Si shows a 5-fold increase of the photocurrent, i.e. 0.5 mA cm- 2 in comparison to 0.1 mA cm- 2 for the undoped samples. The study also reveals that a suitable layer thickness is essential to achieve a beneficial effect of the Si doping.
EAM Import::2019-03-13